Moving beyond “risky behavior”: a qualitative interview study exploring geosocial networking app use by sexual minority men and women in the UK and USA - Madden, Hannah; Timpson, Hannah; Breny, Jean; Hope, Vivian; Porcellato, Lorna (International Journal of Sexual Health, 2025)
Objective: Research on use of geosocial networking (GSN) applications (e.g. Grindr, Tinder) by sexual minorities has primarily focused on risky behavior and negative health outcomes (e.g. sexually transmitted infections/HIV, drugs, alcohol, violence) among men who have sex with men. Taking a sex-positive approach, this study aimed to understand how sexual minority GSN app users in the UK and USA perceive impacts on their health and how they manage potential risks. Differences between countries and genders are explored. Design and methods: Qualitative, cross-cultural study in Merseyside (UK) and Connecticut (USA). Photo-elicitation (fake dating profiles) was used in semi-structured interviews conducted with app users seeking same gender partners (n = 31; 15 women, and 16 men) in 2018-2019. Participants were recruited through local LGBTQ+ organizations, social media and from a previous survey, within a quota sampling framework. Transcripts were analyzed using reflexive thematic analysis. Results: Perceived positive health impacts included social and romantic/sexual connections, boosts to self-esteem, and pleasurable sexual experiences. Some negative outcomes were reported, mainly by men, including rejection and low self-esteem, and racism and discrimination. Participants of all genders used strategies to reduce risks to health. Women were particularly cautious of men on apps. No differences between UK and the USA were noted. Conclusions: GSN apps can enable positive sexual experiences and have the potential to increase social cohesion and improve mental wellbeing for stigmatized sexual minorities. All participants took measures to protect both their physical safety and mental wellbeing. Using a sex-positive health promotion approach could empower app users to build on their personal strengths and resources. Although GSN app companies may need to do more to tackle discrimination, apps show a promising opportunity for reducing isolation and health inequities. The similarity of the findings in both areas suggests evidence from the USA may be applicable in the UK.
Keywords: Clinical psychology; Gerontology; Medicine; Psychology; Qualitative research; Sexual behavior; Sexual minority; Sexual orientation; Social psychology; Social science; Sociology; dept.pch